HUBUNGAN SMARTPHONE ADDICTION DENGAN KUALITAS TIDUR PADA REMAJA DI SMAN 1 MANADO - Bayu Stevanus Rompis; Valen Fridolin Simak; Kristamuliana Kristamuliana (JURNAL KEPERAWATAN, 2022)
Background. Based on comparison with adults, teenagers are more prone to a smartphone. negative impacts for adolescents who use smartphones excessively such as reduced social interactions, frequent delays in work, impaired eye health, and experiencing insomnia or sleep disorders. Poor quality can cause various physiological disorders and can affect the final score of the academic potential test. The purpose of this research is to identify the relationship between addiction to using smartphones and sleep quality in adolescents at SMAN 1 Manado. Method research cross-sectional. Determination of the sample size using the G*Power and obtaining 127 samples and sampling in this study using the Stratified random sampling. Data analysis used univariate analysis and bivariate analysis using chi-square. The results of the statistical test (p = 0.000 or p <0.05) showed the p-value = 0.001 and the OR (Odds Ratio) value of 4.557. The conclusion of this study is that there is a significant relationship between smartphone addiction to sleeping quality in adolescents at SMAN 1 Manado.